The Network of Kiai and Rulers of Surakarta Palace in Islamic Education and Literacy in the 20th Century Ad: A Study of the Wiryadiningrat al-Qur’an Manuscript - Gusmian, Islah; Abdullah, Mustaffa (Jurnal Usuluddin, 2023)
This article examines the network of Kiai (the priest in Islam) and rulers of Surakara palace in the early 20th century AD, under the leadership of Pakubuwono X, in the world of Islamic education and literacy. So far, studies of the Surakarta palace have been limited to social, historical and political studies. In fact, the palace has a network with Kiai, not only in the political context, but also in Islamic education and literacy. The entrance used to analyze this issue is the Wiryadiningrat Qur’an manuscript. This manuscript is chosen because it is not only a religious text, but also part of historical, social and cultural representations as well as relations between subjects that have a social and political basis. Evidence is revealed that Wiryadiningrat, the owner of this Qur’anic manuscript, is a palace official and political adviser to Pakubuwono X. Pakubuwono X, with his authority, has initiated the birth of a modern madrasa (Islamic school) called Mamba’ul Ulum, encouraging the Kiai in this madrasa and the Head of the palace to write Islamic religious texts as learning materials. Moreover, he also provides financial assistance in the operation of the modern madrasa and Islamic literacy. This article shows that the involvement of Kiai in the Surakarta palace in the early 20th century AD is not only in the interest of political legitimacy, but also in the context of developing Islamic education and literacy.